Factors Impacting Teachers’ Job Satisfaction in Chinese Foreign Language Universities: A Case Study of a Foreign Language University in Western China - Lu, Chunxue (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: The study examines the influence of five independent variables—teacher collaboration, disciplinary climate, work goals, working conditions, and stakeholder participation—on a single dependent variable, teacher job satisfaction. Furthermore, the study seeks to determine whether significant differences exist among these variables. Research design, data and methodology: A validity assessment using the Index of Item-Objective Congruence (IOC) and a reliability test with Cronbach’s Alpha (n=30) were conducted. Multiple linear regression analyzed 170 teacher responses from Sichuan International Studies University of Science and Technology. A 14-week Strategic Plan (SP) was implemented with 30 teachers, followed by a paired-sample t-test to compare job satisfaction levels. Results: Multiple linear regression confirmed significant effects of all independent variables on teacher job satisfaction. Furthermore, the results of the paired-sample t-test revealed a significant difference in teacher job satisfaction between the current situation and the expected situation. Conclusions: By identifying critical determinants and testing the effectiveness of strategic interventions, this research contributes to the broader discourse on teacher well-being and professional fulfillment. The implications of these findings extend beyond Sichuan International Studies University of Science and Technology, offering practical recommendations for policymakers and educational administrators aiming to enhance teacher job satisfaction in similar institutional and regional settings.